Mental Health Status of Medical Students in Tehran: A Cross Sectional Study - Mohammad-Reza Sohrabi; Hamid Reza Karimi; Narges Malih; Ali Asghar Keramatinia (Shahid Beheshti University of Medical Sciences, 2015)
Background: Mental health of medical students who will be responsible for community health has great importance. This study was designed to determine the prevalence of probable mental disorders during the internship period of medical students.    Methods: This descriptive cross sectional study evaluated 404 medical students of Shahid Beheshti University of Medical Sciences, in Tehran, the capital of Iran. The data collecting instrument was a self-rated questionnaire including standard mental health questionnaire SCL-90-R, demographic and socio-economic data. The score 0.7 and above were designated as possible cases of mental disorders. Analysis performed by SPSS software, version 14 (SPSS Inc, Chicago, Il, USA). p-value<0.05 was considered significant.   Results: 53.8% of participants were female, and 79.4% were single. From all participants, 14.1% had Global Severity Index (GSI) score more than 0.7. Mean and standard deviation of GSI score was 0.32 (0.27). The frequency of probable mental disorder in medical students was 16.3% in somatization; 24.5% in obsessive-compulsive; 15.6% in interpersonal sensitivity; 16.8% in depression; 18.8% in anxiety; 14.6% in hostility; 11.4% in phobic anxiety; 16.8% in paranoid ideation and 13.9% in psychoticism. Students who had no children, lived in dormitory, had good economic status and were satisfied with their private life and studying course had significantly lower GSI scores.   Conclusion: Between 11 to 24% of the students had mental disorders in different dimensions and economic status, living place and number of children were related to the disorders.